Literature Review: Are Contextual-Based E-books Effective in Learning? - Pratiwi, Ardita Dwiki Putri; Kristiani, K; Noviani, Leny (Universitas Muhammadiyah Surakarta, 2022)
This study aims to analyze and find out whether the use of contextual-based e-books can be effective in improving students' critical thinking skills during the learning process. This type of research is using a literature study approach. The method used in writing this article uses the literature review method, the source of which was obtained on the Google Schoolar website with the issue of the past 4 years. From the 10 articles, it was found that the development of contextual-based learning e- books in some subjects was very effectively used in the learning process by using the ADDIE, 4-D, and Borg and Ball development models. The data collection technique in this research is to collect data using various scientific articles that are relevant to the research topic. The data that has been collected then be analyzed further and presented in scientific writing. In this literature review, the articles that will be used and analyzed were obtained using data from Google Scholar between 2019 and 2022. The results of this literature review show that the use of contextual-based e-books in the learning process is effective for improving students' critical thinking skills.